Analisis Spasial Perubahan Tutupan Lahan Pada Sub Das Bulan Das Jeneberang Tahun 2018 dan 2025: Spatial Analysis of Land Cover Change in the Bulan Sub-Watershed in 2018 and 2025 - Ummu Kultsum; Asikin Muchtar (Jurnal Kehutanan dan Lingkungan, 2026)
This study aims to analyze changes in land cover between 2018 and 2025 in the Bulan Sub-Watershed of the Jeneberang Watershed. The study was conducted from March to April 2026. The method used involved analyzing 2025 Google Earth imagery using ArcGIS 10.8 software. Meanwhile, land cover/land use data for 2018 was obtained from literature using Spot 6 and 7 imagery from 2018 for the same location. After analyzing the imagery, an overall accuracy assessment was conducted to verify the land cover/land use data directly in the field. The research results indicate the area of pine plantation forests in 2018 was 723.02 ha (40.78%) and decreased to 676.78 ha (38.17%) in 2025. Meanwhile, one land cover type that experienced a significant increase was dryland agriculture, which expanded from 240.96 ha (13.59%) in 2018 to 368.95 ha (20.81%) in 2025. 2. Forest cover area decreased from 42.50% in 2018 to 39.34% of the Sub-Watershed’s total area of 1,772.87 ha by 2025. In contrast, non-forest land cover in the Bulan Sub-Watershed has increased, rising by three percentage points from 57.50% in 2018 to 60.66%.